2023
DOI: 10.1039/d3sc01677c
|View full text |Cite
|
Sign up to set email alerts
|

Understanding C–H activation in light alkanes over Cu-MOR zeolites by coupling advanced spectroscopy and temperature-programmed reduction experiments

Karoline Kvande,
Beatrice Garetto,
Gabriele Deplano
et al.

Abstract: Temperature-programmed-reduction studies combined with advanced spectroscopy and data analysis methods shed light into the dynamic changes of Cu-speciation during light alkane selective oxidation over Cu-mordenite zeolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 93 publications
(259 reference statements)
4
11
0
Order By: Relevance
“…The results show a pronounced difference between the reaction of the copper(II) sites with methane and ethane/propane and are in line with the recent report by Kvande et al. showing that Cu II reduction with ethane occurs at lower temperature as compared to the reduction with methane [63] …”
Section: Resultssupporting
confidence: 92%
“…The results show a pronounced difference between the reaction of the copper(II) sites with methane and ethane/propane and are in line with the recent report by Kvande et al. showing that Cu II reduction with ethane occurs at lower temperature as compared to the reduction with methane [63] …”
Section: Resultssupporting
confidence: 92%
“…3650 cm –1 ) using in situ FT-IR, and a concomitant increase in Raman features assigned to Z 2 Cu 2 O from 523 to 673 K in their CHA materials. Similar observations and proposals of monomeric sites converting to dimers have been invoked for MOR using XANES, CO-TPR, electron paramagnetic resonance, operando UV–vis, in situ photoluminescence, and FT-IR . Moreover, the proximity of ZCuOH sites, altered by varying Si/Al and Cu/Al for a given zeolite, has been identified as an important factor for achieving higher methanol yields (per mol Cu). , This proximity requirement is consistent with our finding that only 2Al configurations within Al–Al separations of <8.2 Å (CHA) and <9.4 Å (MOR) convert to dimers (Figure S5.1) at high temperatures.…”
Section: Resultssupporting
confidence: 90%
“…Therefore, the probability ( p i , s ) for species s to form at 2Al site i is p i , s = exp ( Δ G i , s R T ) s A l l .25em C u .25em s p e c i e s .25em exp ( Δ G i , s R T ) This approach does not assume any Al distribution and gives Cu speciation probabilities for all 2Al configurations in each zeolite. To begin, we chose CHA and MOR (other zeolite topologies are discussed later) due to their topological differences (Figure a) and because previous studies have shown that Cu-dimers are the majority Cu motif in MOR at a wide range compositions, , whereas prior experimental and computational results show Cu preferentially occupies the 6MR in CHA forming Z 2 Cu monomers. ,,,,, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations